(untitled) (Revista Brasileira Multidisciplinar, 2026)
Dragon fruit plants of the Hylocereus genus, epiphytic cacti adapted to shaded environments, require specific light interception conditions for optimal development in commercial cultivation. This study evaluated the initial vegetative growth of Hylocereus undatus (red-skinned, white-fleshed dragon fruit) under different shading levels (full sun, intercropping with banana, 30% shade cloth, and 50% shade cloth) in an organic production system, using a randomized complete block design with five replications. Results showed that 50% shading provided the greatest total cladode length (106.2 cm), significantly outperforming other treatments (p<0.05), while full sun cultivation showed the lowest growth (28.65 cm), demonstrating sensitivity to direct radiation. The banana intercropping and 30% shade treatments showed no statistical difference between them, suggesting insufficient light interception for optimal development. Negative correlations between high temperatures and growth (p<0.05) reinforced the need for thermal protection, particularly during months with temperatures exceeding 35°C (95°F). Artificial 50% shading proved to be the most favorable condition for initial dragon fruit establishment in organic systems, ensuring vegetative vigor and mitigating environmental stress, while full sun exposure compromised plant development. These results provide technical support for sustainable crop management, aligning productivity with agroecological resilience.